“And then I got strangled”: Dangerous trends of sexual choking among young people - Kero, Katja; Lauerma, Hannu; Wahlsten, Pia (Wiley, 2026)
Sexual choking has become increasingly normalized among young people, largely driven by media, pornography, and peer norms. Although often framed as consensual, breath-control practices are physiologically unpredictable and can cause rapid loss of consciousness, brain injury, or even death within seconds. Once consciousness is lost, consent cannot be given or verified. Clinical and forensic experience in Finland indicates that choking is frequently reported in younger patients, yet national prevalence data are lacking. We argue that sexual choking is never medically safe, that clinicians should routinely ask about it, assess for injury, and provide clear risk counseling, and that medical ethics require engagement with harmful trends in patient care. Further research is needed to quantify prevalence and harms in Finland.